RANCANG BANGUN APLIKASI PIUTANG PADA KANTOR PEMASARAN TANAH KAVLING PANDUGO 200 SURABAYA - Ubaid, Abdulloh; Tjandrarini, A. B.; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Pandugo 200 is a company that engaged in the sale and purchase of land plots for cash and credit in Surabaya and Sidoarjo with problems 60,62% of uncollected accounts receivable. This is caused of nothing recording recapitulation of due date and many payment record books of the company. Consequently, the procedure to remind the customer to be hampered and the filing of the customer's credit worthiness decision could not be known immediately. In this study, these problems solved by building accounts receivable application at Pandugo 200 usinG Systems Development Life Cycle (SDLC). Accounts receivable applications that has built able to monitor customer accounts receivable as a reminder of the company through the Short Message Service (SMS), presents a recording of integrated payment on each payment book, the payment classification, and a monitoring report each month accounts. Based on the testing system is known that the Account Receivable Application Pandugo 200 Surabaya has been run appropriately. The application is able to send SMS remainder of credit collection and generate accounts receivable credit reports, customer payment reports, the target of accounts receivables, the difference between the amount of revenue target information with payment claims, and track record of customer payments.